Scapular muscles contribution during arm abduction: comparison of healthy subjects and patients with forward head posture (Physical Treatments, 2012)
Background and Objective: Although there is evidence for an association between forward head posture and scapular muscles role, few studies consider the issue how this relationship might be. Therefore, the purpose of this study was to compare contribution ratio of scapular muscle during arm abduction in subjects with and without forward head posture. Methods: 18 female (mean age 22.6 years) with head forward posture and 14 healthy female(mean age 22.1) that were students of Tehran University and matched based on variables such as weight, height, age, dominant of upper extremity, voluntarily participated. EMG activity of serratus anterior, upper and lower trapezius was recorded by surface electromyography during arm abduction. The normalized value of each muscle divided on the total of normalized muscle values to calculate contribution ratio. Paired t- test was used to compare EMG activities in each group. Results: The comparison of the contribution ratio of each muscle shown a significant decrease in serratus anterior muscle activity ratio (p = 0 / 002) and a significant increase in upper trapezius muscle activity ratio (p = 0 / 008) in subjects with forward head posture. Conclusion: Reduced contribution of serratus anterior and increased contribution of upper trapezius in subjects with forward head posture confirm that this group muscles work as a force couple muscle. Also the result of this study provides support for the theory that forward head posture can alter scapular muscle activity.